Seasonal variation of vegetative growth, essential oil yield and composition of menthol mint genotypes at southern Brazil (Bioscience Journal, 2012)
Menthol has economic importance to the flavor, food and pharmaceutical industries. Ten menthol mint (Mentha spp) genotypes were assessed for essential oil content and composition at Southern Brazil environmental conditions at two harvest times (February and May). The experimental design was in completely randomized blocks with a 10 x 2 factorial for genotypes and harvest time. The essential oil was obtained by hydrodistillation in a Clevenger apparatus. The essential oil content varied from 0.8 to 5.3% and was greater in February for all the investigated genotypes. The main constituents identified in the essential oil samples were menthol (12 - 92.7%), mentone (2.2 - 56.9%), and neomenthol (2.9 - 12.1%). Menthol levels were superior in May and showed a negative correlation with mentone and neomenthol, which in turn were higher in February. Menthol levels were positively correlated with menthyl acetate. Pulegone, 1.8 cineol, and limonene were also detected in lower concentrations in some genotypes. Thirteen other essential oil constituents were identified as trace elements in essential oil. Mentha canadensis L. showed the highest essential oil content (5.3 % - February and 3.5% - May) as well as the highest menthol content (89.6% - February, 92.7% - May) in both harvests. From the analyzed results, Southern Brazil local environmental conditions are appropriated for menthol production, with two harvests and M. canadensis L. can be recommended as a promising genetic source. The summer harvest (February) favored oil yield, although with a slight decrease in menthol content. The challenge of achieving higher essential oil and menthol yields depends on strategies to increase herb yield by developing innovative agronomic practices.